2008
DOI: 10.1159/000135653
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Genetic Studies from Journals Published in China of Ischemic Stroke in the Han Chinese Population

Abstract: Background: The aim of this study was to confirm the nature and number of genes contributing to stroke risk and qualify the genetic risk of each susceptibility gene in the Han Chinese population. Methods: After collecting all case-control studies related to DNA polymorphism of any candidate gene for ischemic stroke in Han Chinese, strict selection criteria and exclusion criteria were determined and different effect models were used according to the difference in heterogeneity. Meta-analyses were carried out by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 38 publications
1
44
0
2
Order By: Relevance
“…Homozygous presence of D alleles is associated with higher plasma ACE activity. Case-control studies [65,66] revealed that ACE D/D genotypes contribute to ischemic stroke incidence, and this may be due to the effect on essential hypertension. In one study [67] , the association between the ACE D allele and lacunar infarction was positive in the normotensive patients, but the association diminished in hypertensive patients, suggesting an independent effect of ACE D alleles on the lacunar infarction.…”
Section: Renin-angiotensin-aldosterone Systemmentioning
confidence: 99%
“…Homozygous presence of D alleles is associated with higher plasma ACE activity. Case-control studies [65,66] revealed that ACE D/D genotypes contribute to ischemic stroke incidence, and this may be due to the effect on essential hypertension. In one study [67] , the association between the ACE D allele and lacunar infarction was positive in the normotensive patients, but the association diminished in hypertensive patients, suggesting an independent effect of ACE D alleles on the lacunar infarction.…”
Section: Renin-angiotensin-aldosterone Systemmentioning
confidence: 99%
“…We evaluated publication bias by calculating the fail-safe number (Nfs) of meta-analysis. 39 If the Nfs was smaller than the number of observed studies, the meta-analysis result might have a significant publication bias. The statistical significance was set at p 5 0.05 [Nfs0.05 5 ( P Z/1.64) 2 2 k; k means the number of studies included in meta-analysis].…”
Section: Sensitivity Analysis and Publication Biasmentioning
confidence: 99%
“…Hypertension, diabetes mellitus, and dyslipidemia have been demonstrated by others to be related to cerebral infarction, and are recognized as traditional risk factors (Park et al, 2014). Genetics and molecular biology studies have revealed the existence of genetic predisposition to cerebral infarction, and have identified various polymorphisms associated with this condition (Domingues-Montanari et al, 2008;Xu et al, 2008). Atherosclerosis, the inflammatory response, and impaired vascular endothelial function play an important role in the development of cerebral infarction (Pucci et al, 2011;Soskić et al, 2011).…”
Section: Discussionmentioning
confidence: 99%